An Eschatological Study of Jerusalem in Biblical and Quranic Literature. Issue 3 (1st September 2020) - Lubis, Dahlia; Aziz, Nasaiy; Sinaga, Ali Imran; Sikumbang, Ahmad Tamrin; Yamamah, Ansari; Ridwan, Muhammad; Suharyanto, Agung; Bahri, Saiful; Saragih, M. Yoserizal
Abstract: This study is about Jerusalem in the Bible and Al Quran based on eschatological paradigm (theology/philosophy), which uses two approaches: sociology (geographical and anthropological history analysis) and interpretation (hermeneutical analysis and bil ma'tsur interpretation). Jerusalem is the name of the Holy City of the Abrahamic Religions. This region has been controlled by a number of empires with different geographical boundaries and names over a long period of time. For the Jews, Jerusalem is claimed as the Promised Land. Through a search of several versions of the Bible, a number of commentaries and the main sources (Muslim priests and intellectuals), this study shows eschatologically that Jerusalem in the Bible is not a particular regional name (to a certain extent) but the contextualization of God's Kingdom (saved, renewed earth, harmonious and peaceful). The contextualization of God's Kingdom has something in common with the concept of the promised earth (khilafah) in the Qur'an, as the contextualization of dar as salam, the nickname for countries (dayyar) conquered and claimed to be harmonious and peaceful. In other scenarios of the future, the Kingdom of God and the Caliphate (the promised earth) probably include locations around the Al-Aqsa Mosque that we recognize today.